Manufacturing of Medicate Chewing Gum against Streptococcus Mutans by the Extract of Grape Juice Wastes (Vitis vinifera L.) - Kadhim, Ruaa Jasim (Journal of Science in Medicine and Life, 2024)
The grape juice wastes (GJW) including seeds, peels and flesh of the fruit .The results determination of total phenols in GJW extract 140.13mg/g also flavonoids 25.75mg/g. The zone of inhibition of S. mutans showed the range 16-20mm for different concentration of GJW extract, while GJW extract had MIC values less than 12.5 mg/ml and MBC values 50 mg/ml. The calculated value of median lethal dose (LD50) of GJW extract was assigned to the test mice, which was 6442 mg/kg body weight. Medical gum was manufactured from the following ingredients gum base, glycerine, xylitol, sun flower oil, flavor and color with the addition of the extract tested with different concentration (3.0 and 6.0 mg/g), the release of phenols compounds of chewing gum samples were estimated after each period of crushing the sample of gum in phosphate buffer. It was found that the ratio of the release of tis group of active compounds (phenols) increased with the increase of the duration of crushing gum samples until reaching 100% for all samples after 20 min. The results showed sensory evaluation that samples of gum added to the extract was acceptable and no significant differences was found in comparison to the control treatment.